A Study on the Sports Event Image and Electronic Word-of-Mouth on Behavioral Intentions (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
A Study on the Sports Event Image and Electronic Word-of-Mouth on Behavioral Intentions